Implementation of Zikir as a Spiritual Strengthening Media in Dayah Jamiah Al-Aziziyah Dawah Cadre Training - Arahman, Zulfikar (Society : Jurnal Pengabdian Masyarakat, 2025)
Zikr is an act of worship that is intended to facilitate a closer relationship with Allah SWT and to reinforce individual spiritual connections. This study aims to examine the role of dhikr as a tool for spiritual growth in the training of da'wah personnel at Dayah Jamiah Al-Aziziyah. A qualitative approach with a phenomenological design was employed to gain insight into the implementation of dhikr, its impact on the spirituality of cadres, and the factors that facilitate or impede its effectiveness. Data were collected through the following methods: participatory observation, in-depth interviews, and documentation studies. The findings indicated that zikr is meticulously incorporated into the daily regimen and training program. The cadres report positive outcomes, including an enhanced sense of proximity to Allah, inner tranquility, emotional regulation, and elevated motivation in their preaching. Furthermore, zikr facilitates the strengthening of solidarity and social relations among cadres. However, the consistency of dhikr implementation is occasionally hindered by obstacles such as busy schedules. The success of the program is contingent upon the provision of caregiver support, technical guidance, and adequate facilities. The findings indicate that zikr is not merely a routine act of worship; it is also a tool for character development in the context of da'wah, fostering qualities such as patience, humility, and inclusivity. Ongoing assessment and program refinement are essential to enhance its efficacy. This model is a valuable reference for other Islamic educational institutions seeking to cultivate exemplary da'wah cadres